Analisis Potensi Penularan Tuberkulosis Paru di RW 10 Desa Kedung Waringin, Kecamatan Bojonggede, Kabupaten Bogor - Maharani, Annisa; Siwiendrayanti, Arum (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
The Case Notification Rate at 2019 in Bogor Regency is 274 per 100,000 population. The Success Rate in 2019 was 89,29%, this figure was close to the target of 90%. The condition of the physical environment of the house is one of the factors that can cause the transmission of pulmonary tuberculosis. This objective is to analyze the potential for pulmonary tuberculosis transmission in RW 10 Kedung Waringin Village, Bojonggede District, Bogor Regency. This type of research is quantitative descriptive analytic research. The sampling technique uses accidental sampling. The number of samples is 100 houses. Data analysis in this study used univariate analysis techniques and potential analysis. The results of this study indicate that the most influential variables in the transmission of pulmonary tuberculosis in RW 10 Kedung Waringn Village are ventilation area, humidity, and lighting. Based on the calculation, the average result (mean) for the research variable is 2,5. Where this figure shows that the potential level of pulmonary tuberculosis transmission in RW 10 Kedung Waringin Village is included in the high category. The suggestions from this research are being able to improve the condition of the physical environment of the house so that it fits the criteria for a healthy house, increasing counseling efforts related to tuberculosis and healthy homes, and fostering the community to increase awareness of the surrounding environment if there are pulmonary tuberculosis sufferers.